2020
DOI: 10.1016/j.jcbs.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The moderating roles of psychological flexibility and inflexibility on the mental health impacts of COVID-19 pandemic and lockdown in Italy

Abstract: The Moderating Roles of Psychological Flexibility and Inflexibility on the Mental Health Impacts of COVID-19 Pandemic and Lockdown in Italy. Preliminary data suggest the COVID-19 pandemic has adverse effects on mental health in approximately a quarter of the general population. Few prior studies have identified contextual risk factors and no published study has explored factors that might moderate their adverse effects on mental health. Psychological flexibility is the cornerstone of psychological h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
188
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(211 citation statements)
references
References 51 publications
16
188
2
5
Order By: Relevance
“…In view of the adverse mental health impacts of COVID-19 and associated lockdowns and of the lingering negative psychosocial effects of prior pandemics (e.g., SARS; Hawryluck et al, 2004 ; Taylor, 2019 ), it is essential that effective public health interventions are developed to bolster resilience and promote wellbeing during and in the aftermath of such health crises. Such interventions should target psychological flexibility given the findings from the present study and those from other research indicating that psychological flexibility moderates the adverse impacts of COVID-19 contextual risk factors ( Pakenham et al, 2020 ). Public health ACT-based interventions designed to strengthen psychological flexibility have been shown to promote mental health in a variety of populations using flexible modes of delivery in various contexts: university students via online delivery ( Viskovich and Pakenham, 2020 ), cancer patients via phone ( Hawkes et al, 2014 ), Sudanese refugees using audio-recorded stress-management workshops and a self-help book ( Tol et al, 2020 ), and health anxiety patients via group delivery ( Eilenberg et al, 2016 ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In view of the adverse mental health impacts of COVID-19 and associated lockdowns and of the lingering negative psychosocial effects of prior pandemics (e.g., SARS; Hawryluck et al, 2004 ; Taylor, 2019 ), it is essential that effective public health interventions are developed to bolster resilience and promote wellbeing during and in the aftermath of such health crises. Such interventions should target psychological flexibility given the findings from the present study and those from other research indicating that psychological flexibility moderates the adverse impacts of COVID-19 contextual risk factors ( Pakenham et al, 2020 ). Public health ACT-based interventions designed to strengthen psychological flexibility have been shown to promote mental health in a variety of populations using flexible modes of delivery in various contexts: university students via online delivery ( Viskovich and Pakenham, 2020 ), cancer patients via phone ( Hawkes et al, 2014 ), Sudanese refugees using audio-recorded stress-management workshops and a self-help book ( Tol et al, 2020 ), and health anxiety patients via group delivery ( Eilenberg et al, 2016 ).…”
Section: Discussionmentioning
confidence: 67%
“…Although values, self-as-context, and present moment awareness were significantly associated with better mental health at the bivariate level, these psychological flexibility processes did not emerge as significant mediators or moderators in the link between trait health anxiety and the mental health outcomes. However, in another study values and self-as-context significantly moderated the adverse effects of COVID-19 risk factors on mental health, and the inverse of present moment awareness exacerbated the negative impacts of these contextual factors ( Pakenham et al, 2020 ). It is likely that the prominence and roles of the six contextually sensitive and dynamic psychological flexibility processes will vary according to the nature of the corresponding independent variables and situational factors investigated within a given model.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Additional research identified moderating variables that have an impact on reported mental health during the lockdown (Pakenham et al, 2020). This study included a measure of psychological flexibility described as the ability to adapt to changing situation with a resilient attitude.…”
Section: Introductionmentioning
confidence: 99%